Flow Shop Scheduling Using a Combination of Ant Colony Optimization Algorithm and Tabu Search Algorithm to Minimize Total Tardiness - Hana Merlina Hesti Bestari; Pratya Poeri Suryadhini; Nopendri Nopendri (JTI: Jurnal Teknik Industri, 2024)
This paper addresses the problem of production tardiness on five parallel production floors at PT Garmen X, each with an identical machine arrangement. The proposed method combines Ant Colony Optimization (ACO) and Tabu Search (TS) algorithms for flow shop scheduling problems.  ACO acts as the primary method for finding the optimal solution. At the same time, the Tabu Search algorithm is applied as a local search to improve the quality of the solution found by ACO. The results show significant performance improvement, with a decrease in total tardiness by 88.09% and a reduction in total makespan by 5.08% compared to the existing method. Keywords: Garment, Flow shop, Ant Colony Optimization, Tabu Search, Total Tardiness